Addiction & opiates - Lindesmith, Alfred Ray , 1905-1991 (New Brunswick, New Jersey : Aldine Transaction, 2008)
A study about addiction to opiate-type drugs and their synthetic equivalents. It proposes and elaborates a general theoretical account of the nature of the experiences which generate an addict's characteristic craving for drugs.
1. Method and problem -- 2. The effects of opiates -- 3. Habituation and addiction -- 4. The nature of addiction -- 5. Processes in addiction -- 6. Cure and relapse -- 7. A critique of current views of addiction -- 8. Conclusions, implications, problems -- 9. The problem in the United States during the nineteenth century -- 10. Federal Anti-Narcoticss legislation -- 11. The effects of World War II -- 12. Needed reforms -- 13. Postscript-1968
Originally published: Chicago : Aldine, 1968
Includes bibliographical references (p. 267-287) and index
Keywords: Drug addiction; Narcotics; Opium abuse; Opium; Substance-Related Disorders